Inferioritas Dan Kompensasi Tokoh Utama Dalam Novel Kawi Matin di Negeri Anjing Karya Arafat Nur (Kajian Psikologi Sastra) - Ilmiawan, Nuzul; Zurmailis, Zurmailis; Sukmawati, Noni (Universitas Andalas, 2024)
The purpose of this study is to identify the feelings of inferiority and compensatory behaviors of the main character in the novel Kawi Matin di Negeri Anjing by Arafat Nur, using Alfred Adler's psychology theory. The research methodology employed is qualitative descriptive analysis, involving repeated readings to describe the identified data comprehensively. Through the analysis conducted, it was found that Kawi Matin, as the central character in the novel, faces serious psychological issues stemming from his inferiority complex. These issues include shame, insecurity, fear, doubt, submissive obedience, feelings of inadequacy, and a need for encouragement or support. The inferiority complex possessed by the main character significantly affects his psychological condition. Consequently, the character development of the protagonist is prominently visible from the beginning to the end. Furthermore, Kawi Matin's compensatory actions do not bring significant changes to his life, largely because he lacks a concrete vision for his future. This is due to psychological factors resulting from inferiority of the main character Kawi Matin which greatly influences his personality.